KAP ANALYSIS AND DECISION-MAKING OF NURSES REGARDING SEPSIS ASSESSMENT AND MANAGEMENT IN CRITICALLY ILL PATIENTS - KOUSAR , N; ULLAH , MK; RIAZ , L (Biological and Clinical Sciences Research Journal, 2024)
Sepsis is a life-threatening condition that requires prompt identification and management, particularly in critically ill patients. Nurses play a pivotal role in sepsis management, and their knowledge, attitudes, and practices directly impact patient outcomes. However, there is limited data on the awareness and competency of nurses regarding sepsis assessment and management, especially in low-resource settings. Objective: This study aimed to evaluate the knowledge, attitudes, and practices (KAP) of nurses towards the assessment and management of sepsis in critically ill patients. Methods: A cross-sectional study was conducted in the Intensive Care Unit (ICU) and emergency department of DHQ Hospital, Narowal, from July 2023 to July 2024. A total of 100 ICU and CCU nurses were selected using convenience sampling. Data were collected through a 32-item questionnaire that assessed knowledge, attitudes, and practices related to sepsis. Additionally, the 24-item Nursing Decision-Making Instrument (NDMI) was used to evaluate decision-making skills. Descriptive statistics were calculated, and relationships between variables were analyzed using t-tests and ANOVA. Results: The mean knowledge score was 5.1 ± 1.8, with 83% of nurses demonstrating poor awareness of sepsis. The mean attitude score was 2.0 ± 0.9, with 85% of nurses displaying negative attitudes toward sepsis management. The mean practice score was 79 ± 17.8, with 72% of nurses showing poor practice skills. The mean decision-making score on the NDMI was 63.3 ± 19.6. Qualifications (p=0.010, p=0.00) and work experience (p=0.005, p=0.050) significantly influenced knowledge and practice scores. Moreover, knowledge and practice scores varied significantly with different modes of decision-making (p<0.001, p=0.020). Conclusion: The study revealed that ICU and emergency department nurses had insufficient knowledge, negative attitudes, and inadequate practices concerning sepsis assessment and management. Training programs, targeted educational interventions, and policy reforms are urgently required to improve nurses' competency and decision-making skills in sepsis management, ultimately enhancing patient outcomes.